Plasma membrane-bound tissue inhibitor of metalloproteinases (TIMP)-2 specifically inhibits matrix metalloproteinase 2 (gelatinase A) activated on the cell surface. - Itoh, Y; Ito, A; Iwata, K; Tanzawa, K; Mori, Y; Nagase, H (1998)
The cell-surface activation of pro-matrix metalloproteinase 2 (pro-MMP-2) is considered to be critical for cell migration and invasion. Treatment of human uterine cervical fibroblasts with concanavalin A activates pro-MMP-2 on the cell surface by converting it to the 65-kDa form with a minor form of 45 kDa. However, the 65-kDa MMP-2 was inactivated by tissue inhibitor of metalloproteinases (TIMP)-2 that was bound to the plasma membrane upon concanavalin A treatment. TIMP-2 binds to the plasma membrane through its N-terminal domain by two different modes of interaction as follows: one is sensitive to a hydroxamate (HXM) inhibitor of MMPs and the other is HXM-insensitive. TIMP-2 bound to the membrane in a HXM-insensitive manner, comprising about 40-50% of TIMP-2 on the membrane, is the inhibitor of the cell surface-activated MMP-2. It, however, does not inhibit MMP-3, MMP-9, and the 45-kDa MMP-2 lacking the C-terminal domain. The inhibition of the 65-kDa MMP-2 by TIMP-2 is initiated by the interaction of their C-terminal domains. Subsequently, the MMP-2.TIMP-2 complex is released from the membrane, and the activity of MMP-2 is blocked by TIMP-2. In the presence of collagen types I, II, III, V, or gelatin, the rate of inhibition of the 65-kDa MMP-2 by the membrane-bound TIMP-2 decreased considerably. These results suggest that the pericellular activity of MMP-2 is tightly regulated by membrane-bound TIMP-2 and surrounding extracellular matrix components.